Analysis of random points as a strategy for local optimal improvement in a constructive heuristic - Losqui, Hugo Vinicius Freitas (2019)
This article aims to make an analysis about the NN * algorithm. It was proposed a displacement at the point of base randomness by means of two proposals, in order to obtain an optimization with respect to the NN * algorithm. After the change, gains in the margin were obtained from 24% over what was already in the literature.